PENGARUH LATIHAN CORE STABILITY EXERCISE TERHADAP PENINGKATAN KESEIMBANGAN TUBUH PADA PEMAIN PS.UNDIKMAMATARAM TAHUN 2019 - Susi Yundarwati; Soemardiawan Soemardiawan (P-2623-0291)
The focus of the problem in this study was during the training and competition of the PS players. UNDIKMA Mataram is lacking in passing, dribbling, control, shooting, because it is not good in exercising body balance in doing a body charge that easily falls. Therefore there are exercises Core stability exercise exercises to increase body balance in PS players. UNDIKMA Mataram in 2019. The formula in the research problem is "Is there any effect of core stability exercise on improving body balance in PS players. UNDIKMA Mataram in 2019. "The purpose of this study was to determine the core stability exercise for increasing body balance in PS players. Mataram UNDIKMA 2019 ". The research design used was experimental research "One-Group Pretest-posttest Desaign". This experiment still has external variables that influence the formation of the dependent variable. So the results of experiments which are dependent variables are not solely influenced by the independent variables. The sampling technique uses a population study of 20 players. The results of t-test analysis concluded that "The effect of core stability exercise on increasing body balance in PS players. Mataram UNDIKMA 2019 ". This situation is supported by the results of statistical analysis research which produces a t-test greater than the t-table (10.30> 1,729), so that the null hypothesis (Ho) is rejected. There is no effect of core stability exercise on increasing body balance in PS players. Mataram UNDIKMA 2019. ". Ha accepted, there is an influence there is a core stability exercise to improve body balance in PS players. Mataram UNDIKMA 2019.